Piezochromic Tetracoordinate Boron Complex: Blue‐Shifted and Enhanced Luminescence. (3rd August 2022) - Zou, Junjian; Fang, Yuanyuan; Shen, Yunxia; Xia, Yang; Wang, Kai; Zhang, Cheng; Zhang, Yujian
Abstract: Achieving blueshifted and enhanced emission from purely organic luminophors remains a major challenge. Herein, we report a tetracoordinate boron complex with polymorphism (Y‐phase and O‐phase)‐dependent luminescence. Impressively, the Y‐phase crystals exhibited rare piezochromic luminescent properties such as pressure‐induced blue‐shifted and enhanced emission. The results of theoretical and experimental tests demonstrated that this phenomenon results from the cooperative effect between the restriction of intramolecular motions and alterable charge transfer (CT) behavior during compression. This work provides an ideal model to investigate the optoelectronic properties of boron complexes. Importantly, manipulating the CT behavior through the electrophilicity of boron atoms may become a new principle for the design of piezochromic materials with blueshifted and enhanced emission. Abstract : A tetracoordinate boron complex shows polymorphism‐dependent luminescence. Impressively, Y‐phase crystals showed rare piezochromic luminescent properties: pressure‐induced blue‐shifted and enhanced emission. This phenomenon is due to a cooperative effect between the restriction of intramolecular motions and changes in the charge‐transfer behavior during compression.